The insurance law in Cambodia: the economic modernization and the insurance contract law - Chou Meng (Cogent Business & Management, 2022)
This article begins with a brief overview of the Cambodian Economic Development and offers a brief history of the insurance market industry. The article continues with a more detailed discussion about insurance law and a critical look at the current insurance contract law in Cambodia that has yet to establish a sufficient legal framework for its insurance industry's development. The Insurance Law of Cambodia, particularly the insurance contract law, the definition of insurable interest, the principle of duty of good faith, and its remedies are in flawed condition. A suggestion for future legislation reform has then made in this article. Consequently, the discussion and comparison of the current status of Cambodian insurance law with the well-developed insurance law in common law system will be taken part as a route reference for future reform in Cambodia.
Keywords: 650; Cambodia; Duty of Good Faith; Economic Modernization; Insurable Interest; Insurance Contract